Suicidal behavior in the adolescent population of Ayacucho City: a comparative study between 2003 and 2017 - Vargas-Murga, Horacio (2025)
Objective: To compare the prevalence of suicidal behavior (desire to die, suicidal ideation, suicide planning, and suicide attempts) as well as the gender differences in the adolescent population of the city of Ayacucho in the years 2003 and 2017. Materials and methods: A comparative analysis of secondary sources, using databases from epidemiological studies in mental health conducted by the National Institute of Mental Health «Honorio Delgado-Hideyo Noguchi» in Ayacucho, in 2003 and 2017, is presented. Results: A comparison of prevalence of suicidal behaviors of 624 adolescents in 2003 and 556 in 2017, showed a significant decrease in lifetime suicidal thoughts, from 34.5% in 2003 to 27% in 2017 (p=0.025). Similarly, they declined from 18.9% to 9.2% (p<0.001) in the past year and from 8.8% to 2.5% (p<0.001) in the past month. However, lifetime suicidal ideation slightly increased from 10.2% to 14.2%, although without statistical significance (p=0.117). Likewise, suicide planning experienced a considerable increase from 3.5% to 6.8% (p=0.036), especially among female adolescents, showing the greater vulnerability of this group. A decrease from 2.6% in 2003 to 1.3% in 2017 was observed regarding suicidal attempts, although this reduction was not statistically significant (p=0.137). Females showed higher prevalence than males in terms of suicidal ideation and planning. Conclusions: The findings underscore the need for targeted mental health interventions for adolescents, with particular attention to females, and a comprehensive approach to prevent, detect, and treat suicidal behaviors in a timely manner.